A numerical study on the aero-thermal performance of a slanted-pin-fin cooler under a high-speed-bypass condition. (April 2018) - Kim, Minsung; Ha, Man Yeong; Min, June Kee
Highlights: The performance of a surface air-oil heat exchanger is assessed numerically. Flow and thermal characteristics of slanted-pin fins are assessed. Parametric study on the slanted angle is conducted. Bypass effect on the cooler performance is included. Performance correlations of slanted-pin fin are generated. Abstract: The aero-thermal performance of a slanted-pin fin heat exchanger under high-speed-bypass stream condition was investigated numerically. A channel-shaped computational domain with a periodic boundary condition in the translational direction was adopted. A parametric study was conducted for a Reynolds number ranging from 33, 000 to 164, 000, a bypass height ratio of 1.5–30, and the tilted angle of the fin in a range of 0–45°. The calculated pressure drop and the heat transfer rate are summarized by correlation forms of the friction factor and the Nusselt number. Details of the flow structure and the thermal characteristics of the slanted-pin fin models were assessed as well as the irreversibility loss by the entropy generation. The results showed the advantage of slanted-pin fins for application to aero-engines where the weight penalty and the size of the cooler are critical.